CRISPR/Cas9 Technology for Non-Coding Gene Editing in Schizophrenia Therapeutics: The Recent Progress And Challenges - Mittal, Khushi R.; Jain, Nandini Kumar; Mittal, Swati; Jain, Chakresh Kumar (Current Psychiatry Research and Reviews, 2024)
Within a decade the Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR/Cas9 system), an advanced gene-editing technology became one of the celebrated approaches in modern disease therapeutics and was reported to have a potential role in the alteration of non-coding RNAs segment which are the pivotal causes behind the several mental disorder such as Schizophrenia. In general, Schizophrenia is referred as a neurodevelopmental disorder and symptomatically exhibited by social deficit, cognitive dysfunction, apathy, delusions, hallucinations, etc. At a genomics level large number of loci are susceptible for genetic alteration in schizophrenia and are mostly located in the genome’s non-coding region. With the growing variants and mutations in ncRNA genes (miRNA and lncRNA) strongly associated with schizophrenia, the need to develop a genetic tool to help with the treatment and study of schizophrenia increases. Recently the use of CRISPR/cas9 technology in the productive alteration of non-coding RNAs genes such as miRNA; miR-291, miR-141, and miR-21, lncRNA, lncRNA-21A, AK023948, and LncRNA Rian has been reported. The Cas9 protein and guide RNA (gRNA) together form the CRISPR/Cas9 system is known to be highly specific and efficient for manipulating the impact of gene mutations linked to genomic DNA like ncRNA besides other inheritable genetic diseases. Copy number variations are also found to be linked with schizophrenia. The generation of reciprocal CNVs of 15q13.3 and 16p11.2 in humaninduced pluripotent stem cells (iPSCs) with the CRISPR/Cas 9 system has opened new possibilities. Still, there are some limitations and challenges yet to be defeated, like the blood-brain barrier poses an obstacle to treating mental disorders and ethical issues like genomic DNA manipulation of eggs and embryos. This review brings schizophrenia-associated ncRNAs and CRISPR gene-editing technology for the non-coding parts of the genomic DNA together and recent challenges.
Keywords: CRISPR/cas9 system